Награды: энциклопедический путеводитель по истории Российских наград / А. А. Кузнецов - Кузнецов Александр Александрович (Мир познания, 1999)
Экземпляры: ЦБ (1999 г.) / Инвентарный номер: 32585 / Цена: 59.62 / Авт.знак: К 89 / ГРНТИ: 03.81.27 / ББК: 63.2